Association of Albumin to Creatinine Ratio with Severity of Coronary Artery Disease - Islam, Lohani Md Tajul; Abdullah, Abu Sadique; Al Azad, Sarker Md Alauddin; Jubayer, Mohammad; Amin, Md Gaffar; Sabah, KM N; Rahman, Mohammad Abdur; Khaled, Md Fakhrul Islam; Tushar, Asif Zaman; Chowdhury, Abdul Wadud; et al. (University Heart Journal, 2015)
Coronary artery disease (CAD) is the most common cause of mortality and morbidity all over the world. It is also becoming a significant burden on healthcare service in Bangladesh. Atherosclerosis is the main pathology behind coronary artery disease. Endothelial dysfunction plays a crucial role in the process of atherosclerosis. Microalbuminuria (MA) is a reliable marker of endothelial dysfunction. This is why microalbuminuria is recognized as a simple marker of atherogenic milieu It was a cross sectional analytical study carried out in the department of Cardiology, Dhaka Medical College Hospital, Dhaka during the period of May, 2013 to April, 2014. After ethical consideration a total of 120 patients with IHD admitted in the department of Cardiology who fulfilled the inclusion and exclusion criteria and underwent coronary angiogram were taken as sampling population by purposive sampling. 1st morning spot urine sample was taken for measurement of ACR.Microalbumnuria was measured by rate nephelometry using Behring protein analyzer. All the study subjects were placed into two groups according to ACR value (group I- positive urinary ACR >30 mg/g & group II-Normal urinary ACR <30 mg/g). Angiographic severity of coronary artery disease was assessed by vessel score and stenosis score. Age and sex distribution of the subjects in two groups with MA and without MA were similar. No significant difference was observed between two groups with regard to smoking, dyslipidaemia, hypertension and family history of IHD. Prevalence of diabetes mellitus was significantly more in subjects with MA than without MA (60% vs 33.9%, p=0.006). All 40 patients of group I had significant CAD. 57(71.2%) patients of group II had significant CAD and 23(28.8%) patients had no significant CAD. The difference was highly significant (p<0.001). Single vessel involvement was significantly more frequent in subjects of group II than group I (35.0% vs15.0%, p=0.022) Double vessel involvement was more in group I than group II, but the difference was not statistically significant (36.8% vs 32.40%,p=0.641).Triple vessel involvement was significantly more frequent in subjects of group I than group II (50.0% vs10.7%, p<0.001). The mean stenosis score of group I was significantly higher than group II (95% CI 4.966 to 2.809, p<0.001). The mean ±SD total coronary vessel score of group I was 16.60±4.75 with a range of 7.0-21.0 and mean ±SD total coronary vessel score of group II was 8.26±6.24 with a range of 0.0-21.0. The mean total score of group I wassignificantly higher than group II (95% CI 10.558 to 6.117, p<0.001). Patient with microalbuminuria has more extensive and complex angiographic coronary artery disease compared to those without microalbuminuria. University Heart Journal Vol. 10, No. 1, January 2014; 18-22